Smart Urban Agriculture - Anne-Sophie Christmann; Valerie Graf-Drasch; Ricarda Schäfer (Business & Information Systems Engineering, 2024)
Given cities' rising environmental problems and increasing food insecurity, innovative organizational endeavors such as urban agriculture present a chance for additional ecosystem services and food production. However, urban spaces are hostile as they jeopardize the availability of air, water, or soil. While digital innovations enable the management of scarce resources in traditional agricultural contexts, little is known about their applicability in urban agriculture endeavors. This study proposes a multi-layer taxonomy focusing on digital technologies, data, and different approaches in urban agriculture, as well as 20 organizational readiness factors derived with academics and practitioners from the smart urban agriculture domain. Combining both perspectives, the study sheds light on the nature of smart urban agriculture and ways to leverage its economic, ecological, and social value.
Keywords: 000; Digital opportunities; Smart urban agriculture; Taxonomy; Readiness